Insider Trading Around Dividend Announcements: Theory and Evidence. - John, Kose; Lang, Larry H P (Journal of Finance, 1991)
The informational role of strategic insider trading around corporate dividend announcements is studied based on the efficient equilibrium in a signaling model with endogenous insider trading. Insider trading immediately prior to the announcement of dividend initiations has significant explanatory power. For firms with insider selling prior to the dividend initiation announcement, the excess returns are negative and significantly lower than for the remaining firms (with no insider trading or just insider buying) as implied by the authors' model. Another implication is that dividend increases may elicit a positive or negative stock price response depending on the firm's investment opportunities.